Levocarnitine Use Is Associated With Improvement in Sarcopenia in Patients With Liver Cirrhosis. Issue 3 (22nd January 2019) - Hiramatsu, Akira; Aikata, Hiroshi; Uchikawa, Shinsuke; Ohya, Kazuki; Kodama, Kenichiro; Nishida, Yuno; Daijo, Kana; Osawa, Mitsutaka; Teraoka, Yuji; Honda, Fumi; Inagaki, Yuki; Morio, Kei; et al.
Abstract : Although the effect of levocarnitine (L‐carnitine) on hyperammonemia has been reported in patients with liver cirrhosis (LC), its effect on sarcopenia remains to be elucidated. We assessed the effects of L‐carnitine on sarcopenia in patients with LC. We retrospectively evaluated 52 patients with LC who were treated with L‐carnitine for more than 3 months between February 2013 and June 2017. Computed tomography was used to measure the cross‐sectional area of the skeletal muscles at the level of the third lumbar vertebra. The relative change in skeletal muscle index (SMI) per year (ΔSMI/year) was computed in each patient. We evaluated the relationship between ΔSMI/year and various parameters, such as age, sex, liver functional reserve, and dose of L‐carnitine. The median ΔSMI/year for all patients was −0.22%. The ΔSMI/year values in Child‐Pugh classes A, B, and C were not significantly different among the three groups. There was no significant relationship between ΔSMI/year and sex, age, body mass index, and sarcopenia. Multivariate analysis showed that only a high dose of L‐carnitine (odds ratio [OR], 4.812; 95% confidence interval [CI], 1.233‐18.784; P = 0.024) was associated with increased muscle mass. The L‐carnitine high‐dose group included a significantly larger number of patients with increased muscle mass compared with the low‐dose group (OR, 3.568; 95% CI, 1.138‐11.185; P = 0.027). Administration of L‐carnitine led to a significant and gradual reduction in serum ammonia levels. Conclusion: L‐carnitine seems to suppress the progression of sarcopenia dose dependently, and this was noted to be associated with the improvement of hyperammonemia in patients with LC. Abstract : L‐carnitine seems to suppress the progression of sarcopenia dose dependently and this was noted to be associated with improvement of hyperammonemia in patients with LC.